Gossip in the Qur’an: Analysis of Ibn ‘Āsyūr Maqāṣid Al-Qur’ān in QS. Al-Hujurāt: 12 and An-Nūr: 11,16 and 19 - Amalia, Widayatul; Muttaqin, Khairul; Nurhayati, Nurhayati; Rohman, Miftahur; Muthoharoh, Wafiyyah (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2025)
The phenomenon of gossip often occurs in society, both directly and through social media, leading to negative impacts on individuals and society. Gossip is not a new phenomenon, as it also took place during the time of the Prophet Muhammad (PBUH), one example being the gossip that affected the Prophet’s wife, Siti Aisyah (RA), which is recorded in QS. an-Nūr (24), verses 11-19. These verses not only serve as a warning to humanity but also contain maqṣud (objectives) that can provide valuable lessons in life, including how to deal with gossip. This article employs a qualitative method with a library research approach. The findings of this article indicate that the verses about gossip in the classification of maqāṣid al-Qur’ān according to Ṭahir Ibn ‘Āsyūr include: first, improving faith (akidah); second, instilling good character (akhlak); third, safeguarding the well-being of the community by providing rules, as stated in QS. al-Hujurāt (49), verse 12, and QS. an-Nūr (24), verses 16 and 19; fourth, presenting historical stories as a lesson for humanity to prevent repetition of past mistakes; fifth, serving as a reminder to humanity not to violate what has been forbidden by Allah SWT, including gossip; sixth, informing that every action of a human being will be rewarded accordingly; and seventh, as a miracle that must be believed by Muslims. Fenomena gosip kerap terjadi dalam sosial masyarakat, baik secara langsung maupun melaui media sosial, sehingga menimbulkan dampak negatif pada individu ataupun sosial. Gosip bukan fenomena baru, karena pada masa Rasulullah saw. gosip juga terjadi, salah satunya menimpa istri Nabi saw. Siti Aisyah r.a. yang diabadikan dalam QS. an-Nūr (24) ayat 11-19. Ayat ini tidak hanya sebagai peringatan kepada umat manusia, tetapi juga mengandung maqāṣid (tujuan) yang akan dapat menjadi ibrah dalam kehidupan, termasuk dalam menyikapi gosip. Artikel ini menggunakan metode kualitatif dengan jenis library research. Hasil artikel ini menunjukkan bahwa ayat-ayat tentang gosip dalam klasifikasi maqāṣid al-Qur’ān Ṭahir Ibn ‘Āsyūr, yaitu pertama, memperbaiki akidah; kedua, menanamkan akhlak yang baik; ketiga, menjaga kemaslahatan umat dengan memberikan aturan sebagaiman disampaikan dalam QS. al-Hujurāt (49) ayat 12, dan QS. an-Nūr (24) ayat 16, 19; keempat, kisah-kisah terdahulu sebagai gambaran kepada manusia agar tidak terulang kembali; kelima, sebagai peringatan kepada manusia agar tidak melanggar apa yang sudah dilarang oleh Allah Swt. termasuk gosip; keenam, menginformasikan bahwa segala perbuatan manusia akan mendapatkan balasan; ketujuh, sebagai mukjizat yang wajib diyakini oleh umat muslim.